Time Histograms with Select and Zoom for Creating Visual Representation of Data Set for Managers - Savoska, Snezana; Loshkovska, Suzana; Blazeski, Vlatko (My University, 2008)
Histograms are very useful tools for visualization and the most frequently used analysis techniques for managers because they show distribution of value over a data dimension. Although 2D and 3D standard histograms show the distribution of value over data dimensions, they do not consider the time as additional dimension. In this paper, we present Time Histograms with Select&Zoom technique which is an extended technique of standard histograms with possibility of selecting time step for zooming with slider in second – zoom window.
Keywords: Time Histograms, Select and Zoom, Data Visualization for Management